2012
DOI: 10.1017/s0007114512000542
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of severe methotrexate-induced intestinal damage using enteral n-3 fatty acids

Abstract: Growing evidence suggests that n-3 PUFA and their specific lipid mediators can reduce the activity of inflammatory processes. In the present study, we evaluated the effects of oral n-3 PUFA supplementation on intestinal structural changes, enterocyte proliferation and apoptosis during methotrexate (MTX)-induced intestinal damage in the rat. A total of thirty-two male rats were divided into four experimental groups: control (CONTR) rats; CONTR-n-3 PUFA rats treated with oral administration of n-3 PUFA at a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…In humans, it is characterized by weight loss, generalized infection and longer hospitalization time [ 12 , 13 ]. In mice, the inflammation site depends on the mouse strain and the general effects of the disease [ 21 , 22 ]. In a previous study with BALB/c mice, gut inflammation was observed mainly in the terminal jejunum and ileum, with significant weight loss [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, it is characterized by weight loss, generalized infection and longer hospitalization time [ 12 , 13 ]. In mice, the inflammation site depends on the mouse strain and the general effects of the disease [ 21 , 22 ]. In a previous study with BALB/c mice, gut inflammation was observed mainly in the terminal jejunum and ileum, with significant weight loss [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, mice injected with 5-FU and fed a diet with n-3 showed decreased mucosal inflammation with maintenance of the villus and crypt length, making the MUC + n-3 mice similar to the CTL mice. It was previously described that n-3 FA consumption significantly attenuates intestinal injury [ 22 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hLZ-milk fed pigs also had deeper crypts, which contain the multicomponent local stem cells that give rise to terminally differentiated functional cells including enterocytes [38]. Previous studies show during intestinal inflammation increased crypt depth is closely correlated with increased crypt cell proliferation and improved intestinal recovery [39].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 improved neutrophil function in cancer patients receiving chemotherapy [53]. Moreover, enteral n-3 polyunsaturated fatty acids reversed mucosal intestinal damage and improved intestinal recovery following MTX-induced intestinal damage in rats which could be clinically beneficial in preventing intestinal damage and in stimulating intestinal recovery in patients with chemotherapy-induced mucositis [54].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%